Teachers as Cognitive Mediators and Promotors of Meaningful Learning - Ferreira, Marco (2019)
The article addresses the importance of cognitive mediation conducted by teachers as an essential resource for developing student autonomy, metacognition and self-regulated learning in order to improve regulation of learning strategies and foster new approaches to learning. Practices and experiences of Mediated Learning enhance differentiated instruction where teachers and students actively co-operate and all students work consistently on challenging activities. The point of departure is a socio-constructivist pedagogy paradigm designed to improve student learning. It also recognizes students as central actors of their own intellectual development. The theoretical basis of the article builds on the analysis of relevant theoretical constructs for teaching and learning.